Socio-Political Influences of Samad Behrangi's Translations on Reformist Movements in Iran in the 1970s - Qessimi, Hamed (International Journal of Humanities and Social Science Research, 2019)
Over the last decades, the possibility of using translation for socio-political agenda and political engagement has taken a great interest in translation studies from the overview of translation theories retraining to subversion or hegemonic context. Moreover, both sociological and sociopolitical approaches to translation highlight the central position of translators themselves as subjectivity and historicity in the process of translating and identifying the translators’ professional trajectories and social positioning as crucial to both process and products of translation activity. Thus, the activist translators use the translation as a knowledge production process that enlightens people to initiate and facilitate socio-political movements which end to social and political changes. This paper investigates the issue of an Iranian activist translator's agency applying Pierre Bourdieu’s concepts (habitus, capital) in the socio-political context of Iran in the 1970s. This study surveys how Samad Behrangi, as a socio-political activist translator and thinker, based on his habitus, selects and translates some texts to transfer new knowledge to the society as cultural capital which intensifies the initiation and the facilitation of social reforms and political movements in Iran in the 1970s. The paper peruses some texts translated by Samad Behrangi to illustrate that he wields his own politics in translation to illuminate Iranians’ thought in contradiction of the imperial regime to stimulate them against institutions of power.